Colorimetric assay for β-lactamase activity using cocktail of penicillin and 4-(2-pyridylazo)resorcinol (PAR)–2Hg2+ complex. (February 2017) - Lee, Suji; Kang, Seungyoon; Eom, Min Sik; Han, Min Su
Abstract: A colorimetric assay method for measuring β-lactamase activity was developed using a cocktail of penicillin and 4-(2-pyridylazo)resorcinol (PAR)–2Hg 2+ complex. The penicilloic acid that hydrolyzed form of penicillin by β-lactamase chelates with mercury ion of PAR–2Hg 2+ complex effectively, conversion of PAR–2Hg 2+ complexes to free PAR induced the color change from red to yellow. Exact measurement of β-lactamase activity can be performed by the spectrophotometric method, and the facile monitoring of β-lactamase activity was possible in real time. Also, this colorimetric method was applied to determine the Michaelis constant ( K m ) of β-lactamase and the IC50 of clavulanic acid. Given the facts that its simplicity and high assay speed, this method may be extended to high-throughput screening of β-lactamase inhibitors. Graphical abstract: Highlights: A colorimetric assay method for β-lactamase was developed using PAR–2Hg 2+ complex. Real-time monitoring of β-lactamase activity was possible using this assay method. A simple and rapid colorimetric assay was possible based on ligand exchange. This assay could be applied for the high-throughput screening of inhibitors.